Overview of syphilis in a northern Brazilian city from 2013 to 2017 - NONATO, OSVALDO CAMPOS DOS SANTOS; Barbosa Martins, Raissa; Bezerra da Silva Sussuarana, Suzana; Albuquerque da Costa, Layra Lucy Maria (Revista de Epidemiologia e Controle de Infecção, 2020)
Justifications and Objectives: Syphilis is the most widespread bacterial infection in thehuman population, being the main form of transmission through sexual contact. It wasanalyzed the epidemiological data of the population of the city of Rio Branco, Acre, Brazil,with a positive diagnosis of syphilis between 2013 and 2017. Methods: This is a descriptive,cross-sectional study, with a quantitative approach applied to data from Acre’s Central PublicHealth Laboratory of the population infected with T. pallidum. Results: Of a total of 5,239people infected with syphilis, 56.8% are female between the ages of 20 and 30 years old andself-declared to have mixed ethnicity. Moreover, 1,006 pregnant women, 43% of whom werebetween 11 and 20 years old and 37.5% were in the 2nd trimester of pregnancy. For live births,107 children with early congenital syphilis were diagnosed. Conclusions: Infectionprevention information should be intensified, especially for people who are unaware of STIsin the city, such as adolescents, elderly people and indigenous populations, in order to avoidsyphilis transmission.